Handbook of Maize: Its Biology - Bennetzen, Jeff L. (Springer, 2017)
Maize is one of the world’s highest value crops, with a multibillion dollar annual contribution to agriculture. The great adaptability and high yield of maize as a food, feed and forage crop have led to its production on a massive scale, with acreage expanding at the expense of other crops. Maize has developed in its non-food usage, comprising a major source of ethanol for fuel in the United States. In addition, maize has occupied center stage in the transgenic plant controversy, serving as one of the first food crops with commercialized transgenic varieties. The release of the genome sequence of maize in 2008 will indicate the structure and gene content of the first average-size plant genome and will be the most complex genome sequenced from any organism to date.